EDWARD ALBEE’S RECEPTION IN GEORGIA - Zhghenti, Inga (Online Journal of Humanities ETAGTSU, 2021)
The aim of the article is to explore the reception of Edward Albee’s drama in the country of Georgia. On the one hand, the proposed work is mainly an attempt to analyze critical reviews related to Albee’s work, whilst, on the other hand, the paper introduces an overview of a number of staged versions of Albee’s The Zoo Story performed in Georgian theatres in an analytical approach and their critical reception. It has to be noted that Edward Albee in Georgia is mostly perceived as a representative of the Absurd Theatre. According to Hungarian critic, Martin Esslin, being the first to use the term “The Theatre of Absurd”, Albee “americanized” the global concept of life’s absurdity accentuated in existentialist philosophy and then echoed in the Theatre of Absurd through ironizing the American Dream and criticizing steady social-economic structures and normalized gender identities within the society. Albee managed to adopt essential and eternal human problems of alienation, loneliness and despair to an American reality. It is clear that the analytical perspectives and approaches declared in the articles written in Georgian significantly influence critical highlights and evaluation as well as aspectual focuses and interpretations demonstrated in the performed versions of the Zoo Story on the Georgian stage. Full Text (PDF)